Cancel Culture Terhadap Peran Abidzar Dalam Film A Business Proposal Pada Akun Instagram @Abidzar73 - Aneka Putri; Silvina Mayasari; Sari Ekowati Hadi (Journal of Innovative and Creativity, 2025)
Cancel culture has become a new phenomenon widely practiced by the public. It is a form of societal rejection againts public figures who are seen as failing to meet societal expetations or social norms. This phenomenon has become a topic of growing discussion, coinciding with the rise in social media users, through which the cancel culture movement spreads. This study discusses the cancel culture phenomenon that affected Abidzar after his role in the movie A Business Proposal. This backlash was widely discussed by the public throught comments on his personal Instagram account, @abidzar73. Using a descriptive methodology with critical discourse analysis, this research aims to identify the forms, reasons, and applications of cancel culture present in those comments. The results indicate that the backlash received by Abidzar was not only related to his acting ability but also to visual standards, public expectations for role representation, and social practices.